MEMBANGUN STRATEGI PEMASARAN DIGITAL PRODUK PERTANIAN ORGANIK DI AGRO ZULFA GARDEN KECAMATAN TARUB - Subrata, Jaka; Faizin, Muhammad yusril; Setiawan, Anton (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This Community Service Program is implemented to assist Agro Zulfa Garden MSMEs in developing digital marketing strategies for organic agricultural products. Partners face various obstacles, such as limited use of social media, not having a website and e-commerce account, and not having a business legality in the form of a Business Identification Number (NIB). This activity includes training in creating e-commerce accounts, designing and implementing websites using WordPress, creating promotional banners, and assisting in issuing NIBs through the OSS platform. The methods used in this activity include submitting a permit letter to the relevant agency as an initial administrative step, field observations to understand business conditions and challenges faced by MSME actors, and direct interviews with MSME owners to obtain more in-depth information about their needs and obstacles in terms of digital marketing. The results of the activity show that partners are able to understand the importance of digital marketing and already have more professional promotional facilities. It is recommended that there be periodic follow-up training, ongoing cooperation between universities, local governments, and MSME actors, and increasing digital literacy through mentoring and learning modules that are easily accessible to MSME actors. This program contributes to expanding market reach and increasing Agro Zulfa Garden's competitiveness in a sustainable manner. Keywords: e-commerce, business legality, digital marketing, organic farming, MSME, website